Intravitreal injection of TA-III with sustained release to simultaneously impart anti-inflammatory, antioxidative, and vascular remodeling activities in diabetic retinopathy - Jie Zhang; Yu Liu; Yu Gong; Yanyu Shangguan; Pengli Wang; Yanlong Bi; Yong Xu; Bo Tao; Bing Li (Materials & Design)
Diabetes negatively impacts vision and retinal function. However, current therapeutic options for diabetic retinopathy (DR) often present limitations, including targeting specific pathways, short duration of action, and need for frequent injections. Timosaponin AIII (TA-III) exhibited the potential of anti-inflammation, anti-oxidative stress and promoting vascular remodeling abilities from bioinformatics analysis tool. Additionally, polyethylene glycol succinimide succinate [PEG-(SS)2]-human serum albumin (HSA) (Hp) hydrogel, known for its excellent biocompatibility and sustained drug release properties, was employed to encapsulate TA-III to exhibit a long-acting, sustained release profile. In vitro results demonstrated that the TA-III/Hp hydrogel upregulated the expression of vascular endothelial growth factor receptor 2 and zonula occludens-1, while reducing the level of vascular endothelial growth factor A. We further observed a significant reduction in the levels of reactive oxygen species, malondialdehyde, interleukin-1β, interleukin-6, and tumor necrosis factor-α under high glucose conditions by using the TA-III/Hp hydrogel in retinal pigment epithelium cells. Notably, intravitreal delivery of TA-III/Hp hydrogel in the DR mouse model effectively increased retinal thickness and numbers of mature blood vessels, while inhibiting oxidative stress and inflammatory factor levels. In conclusion, intravitreal injection of TA-III/Hp hydrogel facilitates sustained release of TA-III, simultaneously providing anti-inflammatory, antioxidative, and vascular remodeling effects in DR.